2011
DOI: 10.1371/journal.pcbi.1002279
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histone Tails in Structural Stability of the Nucleosome

Abstract: Histone tails play an important role in nucleosome structure and dynamics. Here we investigate the effect of truncation of histone tails H3, H4, H2A and H2B on nucleosome structure with 100 ns all-atom molecular dynamics simulations. Tail domains of H3 and H2B show propensity of -helics formation during the intact nucleosome simulation. On truncation of H4 or H2B tails no structural change occurs in histones. However, H3 or H2A tail truncation results in structural alterations in the histone core domain, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 48 publications
9
106
1
Order By: Relevance
“…To study DNA unwrapping, we used the 1KX5 nucleosome with the histone tails removed (85), because the tails may hinder the unwrapping process. The condition of high pH was mimicked by setting all of the titratable sites to their deprotonated states.…”
Section: Methodological Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study DNA unwrapping, we used the 1KX5 nucleosome with the histone tails removed (85), because the tails may hinder the unwrapping process. The condition of high pH was mimicked by setting all of the titratable sites to their deprotonated states.…”
Section: Methodological Detailsmentioning
confidence: 99%
“…Experimentally, it has been shown that under physiological conditions, the unstructured positively charged histone tails collapse onto the negatively charged DNA (83). It has also been shown that histone tails regulate nucleosome mobility and stability (84), and MD simulations have been used to study this regulatory mechanism (85).…”
Section: Nucleosome Histone Tail Collapsementioning
confidence: 99%
“…From the crystal structure, it can be seen that the C-terminal part of H2A (amino acids 80–119), including the α3- and αC-helices, forms a ladle shaped docking domain that constitutes an important interface for interaction with the (H3–H4) 2 -tetramer (8). The very C-terminal amino acids protrude from the globular nucleosome structure and interact with DNA, which is illustrated by molecular dynamics (MD) simulations, revealing stable hydrogen bonds between DNA and the lysines 118 and 119 in H2A (155). This is consistent with the recent finding that H2A monoubiquitination of these residues (Figure 2A) destabilizes nucleosomes during repair of UV-induced DNA damage (156), possibly by neutralization of the negative charge of the ε-amino group.…”
Section: The Influence Of H2a Variants On Nucleosome Stabilitymentioning
confidence: 99%
“…Chromatin is a complex of DNA and histone tetramar proteins that form chromosomes within the nucleus of eukaryotic cells 42 . DNA does not appear in free strands for chromatin rather it is highly condensed and wrapped around histone tetramer proteins in order to fit compactly inside the nucleus 43 . Therefore, DNA strands in chromatin are less accessible for intercalation of Sgr as compared to free DNA strands in ctDNA which is clearly observable from our T-T absorption results.…”
Section: Efficiency Of Drug Release (%)=((A T-t Drug-aunp -A T-tmentioning
confidence: 99%